Pemanfaatan Chatbots dalam Pembelajaran Matematika di Sekolah Dasar: Pengaruh terhadap Pemahaman dan Kemandirian Belajar - Hardika Saputra (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The utilization of technology in education has been increasingly developed, one of which is the use of chatbots in mathematics learning in elementary schools. This study aims to analyze the impact of chatbot usage on students' understanding of mathematics, learning independence, and time management. This research uses the Systematic Literature Review (SLR) method by reviewing various recent studies related to the implementation of chatbots in learning. The findings indicate that the use of chatbots can enhance students' understanding of mathematical concepts, strengthen learning independence, and help students manage their learning time more effectively. Chatbots provide opportunities for students to learn independently, give real-time feedback, and offer flexibility in learning time. The implications of this research emphasize the importance of integrating technology, specifically chatbots, to support more interactive and adaptive mathematics learning in elementary schools. The study also provides recommendations for further development of educational technology to improve the quality of future learning.